2022
DOI: 10.3390/w14203323
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Performance of ANN and SVM Methods for Regional Flood Frequency Analysis in South-East Australia

Abstract: Design flood estimations at ungauged catchments are a challenging task in hydrology. Regional flood frequency analysis (RFFA) is widely used for this purpose. This paper develops artificial intelligence (AI)-based RFFA models (artificial neural networks (ANN) and support vector machine (SVM)) using data from 181 gauged catchments in South-East Australia. Based on an independent testing, it is found that the ANN method outperforms the SVM (the relative error values for the ANN model range 33–54% as compared to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
2

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 60 publications
0
3
2
Order By: Relevance
“…Although the REm values are not remarkably different across the four regression models, LASSO has the smallest REm values overall. The REm values for LASSO are 37%, 44%, 43%, 44%, 43% and 46%, which are generally smaller than similar RFFA studies, such as that by Zalnezhad et al [21], who reported REm values of 42%, 33%, 36%, 40%, 44% and 54% for ARIs of 2, 5, 10, 20, 50 and 100 years, respectively, for an artificial neural networks (ANN)-AM-based RFFA model for south-east Australia. Zalnezhad et al [21] reported median QPred/QObs ratio values in the range of 0.94 to 1.57, which are very close to 1.00 in this study.…”
Section: Resultscontrasting
confidence: 59%
See 2 more Smart Citations
“…Although the REm values are not remarkably different across the four regression models, LASSO has the smallest REm values overall. The REm values for LASSO are 37%, 44%, 43%, 44%, 43% and 46%, which are generally smaller than similar RFFA studies, such as that by Zalnezhad et al [21], who reported REm values of 42%, 33%, 36%, 40%, 44% and 54% for ARIs of 2, 5, 10, 20, 50 and 100 years, respectively, for an artificial neural networks (ANN)-AM-based RFFA model for south-east Australia. Zalnezhad et al [21] reported median QPred/QObs ratio values in the range of 0.94 to 1.57, which are very close to 1.00 in this study.…”
Section: Resultscontrasting
confidence: 59%
“…The REm values for LASSO are 37%, 44%, 43%, 44%, 43% and 46%, which are generally smaller than similar RFFA studies, such as that by Zalnezhad et al [21], who reported REm values of 42%, 33%, 36%, 40%, 44% and 54% for ARIs of 2, 5, 10, 20, 50 and 100 years, respectively, for an artificial neural networks (ANN)-AM-based RFFA model for south-east Australia. Zalnezhad et al [21] reported median QPred/QObs ratio values in the range of 0.94 to 1.57, which are very close to 1.00 in this study. The REm values for LASSO are also smaller than those recom- The RE m (Equation ( 4)) for the four regression models for all six ARIs are shown in Table 4.…”
Section: Resultscontrasting
confidence: 59%
See 1 more Smart Citation
“…Zalnezhad et al compared the performance of SVM and ANN for analyzing flood frequency. 74 Based on independent tests, they found that the ANN method was superior to the SVM method with relative error values of 33 1). For some experimenters who do not have computer programming knowledge but need to apply AI technology to the application of enzyme engineering, simpler and easier-tounderstand models and data migration tools are required.…”
Section: Models and Algorithms For Ai In Lipase Technologymentioning
confidence: 99%
“…However, the support vector machine (SVM) always shows better accuracy than other classifiers due to its strong generalization ability and low computational complexity. Zalnezhad et al compared the performance of SVM and ANN for analyzing flood frequency . Based on independent tests, they found that the ANN method was superior to the SVM method with relative error values of 33–54% for the ANN model and 37–64% for the SVM model.…”
Section: Models and Algorithms For Ai In Lipase Technologymentioning
confidence: 99%